Analisis Faktor Pertumbuhan Kredit Bank Komersil Di Indonesia - Fariz Alfiknacio Abdat; Rika Maryani; Jerry Ananta Ginting; Henny Setyo Lestari; Farah Margaretha (Jurnal Ekonomi, 2024)
This research analyzes the influence of Non-Performing Loans, Loan to Deposit Ratio, Loan Loss Provision, Equity Asset Ratio, Liquidity Ratio, Gross Domestic Product, Inflation, Interest Rate, Bank Capital, and Bank Size on Loan Growth Rate in banking companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. The method used is regression multiple panels with secondary data obtained through purposive sampling, covering 205 financial reports from 41 companies. The results of the analysis using Eviews 12 show that Non-Performing Loans, Loan to Deposit Ratio, Loan Loss Provision, Equity Asset Ratio, Liquidity Ratio, Gross Domestic Product, Inflation, Interest Rate, Bank Capital, and Bank Size have a significant influence on Loan Growth Rate. This research provides important insights into the factors influencing loan growth in the Indonesian banking sector, as well as implications for risk management and banking policy.